2004
DOI: 10.1099/mic.0.26751-0
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of phenotypic variants upon mismatch repair disruption in Pseudomonas aeruginosa

Abstract: MutS is part of the bacterial mismatch repair system that corrects point mutations and small insertions/deletions that fail to be proof-read by DNA polymerase activity. In this work it is shown that the disruption of the P. aeruginosa mutS gene generates the emergence of diverse colony morphologies in contrast with its parental wild-type strain that displayed monomorphic colonies. Interestingly, two of the mutS morphotypes emerged at a high frequency and in a reproducible way and were selected for subsequent c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
40
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 60 publications
(59 reference statements)
5
40
0
Order By: Relevance
“…Certainly, the extremely high prevalence of hypermutable strains found in the present work suggests that hypermutation plays a role in the bacterial adaptation to the lung environment required for long-term persistence because hypermutation increases the rates of generation of any mutant phenotype (not only antibiotic resistance), including those involved in the development of resistance to the host immune system. In this sense, it has recently been found in vitro that mismatch repair disruption in P. aeruginosa determines the emergence at a high frequency of multiple morphological variants resembling what naturally occurs in chronic infections (39). Furthermore, the link between hypermutation and chronic infections seems not to be restricted to just P. aeruginosa, since recent works have found a significantly higher prevalence (14%) of hypermutable Staphylococcus aureus and Haemophilus influenzae strains in CF patients than in patients with other infections (1%) (32,37).…”
Section: Discussionmentioning
confidence: 99%
“…Certainly, the extremely high prevalence of hypermutable strains found in the present work suggests that hypermutation plays a role in the bacterial adaptation to the lung environment required for long-term persistence because hypermutation increases the rates of generation of any mutant phenotype (not only antibiotic resistance), including those involved in the development of resistance to the host immune system. In this sense, it has recently been found in vitro that mismatch repair disruption in P. aeruginosa determines the emergence at a high frequency of multiple morphological variants resembling what naturally occurs in chronic infections (39). Furthermore, the link between hypermutation and chronic infections seems not to be restricted to just P. aeruginosa, since recent works have found a significantly higher prevalence (14%) of hypermutable Staphylococcus aureus and Haemophilus influenzae strains in CF patients than in patients with other infections (1%) (32,37).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the emergence of various morphotypic variants has been described for a P. aeruginosa strain with a disrupted mutS gene (42). While the component MutS is generally implicated in the detection of DNA mismatches and initiation of the MMR machinery, the function of MutL is to make a connection between the recognition of a mismatch and the excision of the mismatch from the strand within which it is contained (19).…”
Section: Vol 52 2008 Thymidine-dependent S Aureus Scvs Are Hypermumentioning
confidence: 99%
“…Sequence of mucA and lasR in consecutive CF P. aeruginosa isolates from different time points of the chronic lung infection Inactivation of the MMR system was shown in vitro to favour the emergence of mucA22 and lasR mutants (Smania et al, 2004;Lujan et al, 2007;Moyano et al, 2007), and an association between hypermutability and mucoidy has been reported in clinical CF isolates (Waine et al, 2008).…”
Section: Sequences Of Anti-mutator Genes In Consecutive Cf P Aeruginmentioning
confidence: 99%
“…Inactivation of the MMR system was shown to favour the emergence in vitro of phenotypic variants considered typical markers of CF lung infection such as mucoidy due to mutations in mucA and loss of quorum sensing due to mutations in lasR (Smania et al, 2004). However, the time sequence in which the hypermutable, mucoid and quorum-sensing negative phenotypes emerge during chronic lung infection has not been investigated before in clinical CF P. aeruginosa isolates.…”
mentioning
confidence: 99%